2010
DOI: 10.1186/1471-2407-10-217
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylated 14-3-3-σ and ESR1 gene promoters in serum as candidate biomarkers for the diagnosis and treatment efficacy of breast cancer metastasis

Abstract: BackgroundNumerous hypermethylated genes have been reported in breast cancer, and the silencing of these genes plays an important role in carcinogenesis, tumor progression and diagnosis. These hypermethylated promoters are very rarely found in normal breast. It has been suggested that aberrant hypermethylation may be useful as a biomarker, with implications for breast cancer etiology, diagnosis, and management. The relationship between primary neoplasm and metastasis remains largely unknown. There has been no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 43 publications
(61 reference statements)
2
46
0
1
Order By: Relevance
“…The 14-3-3 proteins are a family of widely expressed regulatory molecules in signal transduction, cell cycle control (G2 checkpoint) and apoptotic cell death. 14-3-3-sigma sequesters the cdc2-cyclin B1 complex in the cytoplasm, resulting in G2 arrest [19,114]. It is one of the most frequent and early methylated genes in the progression from normal to atypical hyperplasia, to DCIS and finally to invasive carcinoma.…”
Section: Cell Cycle Regulationmentioning
confidence: 99%
“…The 14-3-3 proteins are a family of widely expressed regulatory molecules in signal transduction, cell cycle control (G2 checkpoint) and apoptotic cell death. 14-3-3-sigma sequesters the cdc2-cyclin B1 complex in the cytoplasm, resulting in G2 arrest [19,114]. It is one of the most frequent and early methylated genes in the progression from normal to atypical hyperplasia, to DCIS and finally to invasive carcinoma.…”
Section: Cell Cycle Regulationmentioning
confidence: 99%
“…The CpG methylation signatures have been reported to be the potential diagnostic, prognostic, and predictive tools for breast cancer (Jovanovic et al, 2010;Parrella, 2010). The methylation analysis also improves early breast cancer detection (Caldeira et al, 2006;Noetzel et al, 2008;Henneges et al, 2009;Seniski et al, 2009;Veeck et al, 2009;Wu et al, 2010;Zurita et al, 2010;Suijkerbuijk et al, 2011). However, the relationship between MKP-1 gene expression and methylation in breast cancer remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In a genome-scale screen, IFFO1 methylation was identified as a meaningful marker for ovarian cancer that showed, in a subsequent validation study, similar post-resection kinetics to CA 125 [162]. Further small follow-up studies identified concordances of serum methylation markers and disease status for RASSF1A and ovarian cancer [163], for ESR1 and 14-3-3-sigma and breast cancer [164], and for p16INK4a and colorectal cancer [165]. Presurgery RUNX3 methylation was predictive for the relapse of colorectal cancer [166] and serum RASSF1A methylation status one year after breast cancer surgery indicated the long-term outcome [167].…”
Section: Epigenetic Changes On Cell-free Dnamentioning
confidence: 91%